Fear during the Covid-19 Pandemic - Mihai Pascaru (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
This study will present some results of an on-line survey conducted by the author on a sample of 1640 subjects. The analysis of the results from the perspective of fear determinants during COVID-19 pandemic has revealed that being a less educated, older (but not over 70 years), social-network-informed, widow, living in a rural area, may result in an increased level of fear. Direct experience with the virus does not result in significant differences in fear level according to our findings. The impact analysis of fear on attitudinal compliance revealed that higher levels of fear may result in higher levels of compliance with preventive measures and in more willingness to get vaccinated.